Evaluation Of Healthcare Services Of Medical Universities\' Websites In Line With E-Government - Mehrdad Farzandipour; Zahra Meidani; Hamidreza Gilasi (Tehran University of Medical Sciences, 2014)
Background and Aim: Due to the role of websites in delivering e-services, this study aims to benchmark rendering healthcare services at medical universities' websites based on Chandler and Emanuel's four-stage e-government maturity model. Materials and Methods: This is a descriptive, cross-sectional study which was conducted using content analysis and benchmarking to evaluate the delivery of healthcare services through medical universities websites towards e-government maturity including Information, Interaction, Transaction and Integration services in 1390.  Results: The results of the study revealed that type I universities were moderate in giving information, and type II and III universities were poor in this regard. Websites of type I, II and III universities were poor in interaction with scores 1.4±0.73, 1.3±0.75 and 1.2±0.62, respectively. The score of all universities was weak in transaction and integration of healthcare services (mean 1 ±0).  Conclusion: Medical universities' websites have lagged behind to render e-services. Due to the challenges of health services and information, realization of e-government in healthcare arena requires special consideration. Adopting e-government in other settings, detecting barriers, and formulating related laws and policies can pave the way to achieve e-government in healthcare arena